Mutant analysis shows that the Ca2+-induced K+ current shuts off one type of excitation in Paramecium. - Saimi, Y (1983)
Two mutants of Paramecium tetraurelia, called "pantophobiacs," were found to lack most of the slow Ca2+-induced K+ outward current. Passive properties, the transient Ca2+ inward current, and the fast depolarization-induced K+ outward current remain normal. The mutant defect reduces the ability to shut off a normal, excited state of the membrane and results in repeated, long backward swimming instead of the wild-type jerks in response to a variety of ions, to heat, and to touch.